2021
DOI: 10.1016/j.jtemb.2021.126789
|View full text |Cite
|
Sign up to set email alerts
|

A literature review on beneficial role of vitamins and trace elements: Evidence from published clinical studies

Abstract: COVID-19 is a kind of SARS-CoV-2 viral infectious pneumonia. This research aims to perform a bibliometric analysis of the published studies of vitamins and trace elements in the Scopus database with a special focus on COVID-19 disease. To achieve the goal of the study, network and density visualizations were used to introduce an overall picture of the published literature. Following the bibliometric analysis, we discuss the potential benefits of vitamins and trace elements on immune system function and COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 112 publications
(130 reference statements)
0
30
0
Order By: Relevance
“…It inhibits the RNA polymerase required to replicate RNA viruses such as those containing coronavirus. 34 Furthermore, Cu is an important micronutrient for viral infections for both pathogens and hosts. It has been shown to play an important role in immunity through its involvement in the production and differentiation of immune cells such as T-cell proliferation and natural killer activity in the host.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It inhibits the RNA polymerase required to replicate RNA viruses such as those containing coronavirus. 34 Furthermore, Cu is an important micronutrient for viral infections for both pathogens and hosts. It has been shown to play an important role in immunity through its involvement in the production and differentiation of immune cells such as T-cell proliferation and natural killer activity in the host.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to play an important role in immunity through its involvement in the production and differentiation of immune cells such as T-cell proliferation and natural killer activity in the host. 34 The Cu/Zn ratio is clinically more important than the concentration of these metals separately. 35 Previous studies have shown that Cu and Zn deficiencies predispose to infections, whereas systemic inflammation and infections result in a decreased serum Zn concentration during the acute-phase response because of the redistribution of serum Zn to the liver and other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Although the effects of micronutrients on neutrophil functions are not clear, micronutrients such as Fe, Zn, Cu, Se, among others can influence various components of innate immunity [2] , [5] , [30] , [31] , [32] . For example, the contributions of trace elements to the immune system are observed both to regulate the number and function of innate immune cells (natural killer cells (NKCs), macrophages, monocytes, and neutrophils) and to assist the production of pro-inflammatory and anti-inflammatory cytokines in responses to inflammation (adaptive immunity) [10] , [33] , [34] , [35] , [36] , [37] . In this sense, many studies have reported changes in metals levels in the host’s biological system during viral infections [2] , [5] , [6] , [17] , [30] , [32] , [38] , [39] , [40] , [41] .…”
Section: Complex Interaction Between Trace Elements and Viral Infectionmentioning
confidence: 99%
“…Initially, it was believed that COVID-19 infection only affected the respiratory tract, however the appearance of neurological, hematological, and gastrointestinal, symptoms attested its more systemic character [4] , [8] , [9] , [10] , [11] . For example, it was reported that nearly 40% of critically ill COVID-19 patients presented strokes, cognitive dysfunction, depression, psychosis, and delirium, suggesting that this virus may predispose to several neurological disorders [4] , [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Spencer et al (30) used bibliometric and visualization techniques to identify and explore the uptake of Fanshel and Bush (7), and Torrance et al (8) over time within the health state valuation literature. Bibliometrics and visualization techniques are forming new methods to review large scientific databases, enabling researchers to create scientific maps reflecting the links between authors, references, and keywords to gain an overall picture of the evidence base (31,32).…”
Section: Introductionmentioning
confidence: 99%